An Application of Screw Theory to the Jerk Analysis of a Two-Degrees-of-Freedom Parallel Wrist - Jaime Gallardo-Alvarado; Ramón Rodríguez-Castro; Martín Caudillo-Ramírez; Luciano Pérez-González (Robotics, 2015)
In this work the velocity, acceleration, and jerk analyses of a two-degrees-of-freedom parallel wrist are approached by means of the theory of screws. For the sake of completeness, the finite kinematics of the manipulator is also investigated. As far as the authors are aware, the equation of jerk in screw form of the robot at hand is introduced by the first time in this contribution. In order to exemplify the method, a case study is included. The numerical example is verified with the aid of commercially available software.